Qawā’id Fiqhiyyah as Islamic Epistemology and its Application at Marriage Law in Indonesia - Ansori Ansori (Institut Agama Islam Negeri Batusangkar, 2022)
Qawā'id fiqhiyyah is a scientific field related to the methodology and philosophy of Islamic law. Qawā'id fiqhiyyah has been widely used as a basis to solve legal problems in society. As a philosophy, qawā'id fiqhiyyah is used as the basis for philosophical thinking to develop and discover new laws. This function of qawā'id fiqhiyyah is closely related to epistemological studies. This paper analyzes and proves that scientifically qawā'id fiqhiyyah is an epistemology in Islamic law. In addition, this paper also provides concrete evidence of the use of qawā'id fiqhiyyah as an epistemology of Islamic law. The study of qawā'id fiqhiyyah as an epistemology refers to the epistemological concept of Muḥammad 'Ābid al-Jābiriy. The examples of its use or application to the provisions of marriage law are contained in Law Number 1 of 1974 and the Compilation of Islamic Law. It shows that the function of qawā'id fiqhiyyah according to the epistemological concept of al-Jābiriy, is as guardians and developers of legal texts (Al-Qur'an and Hadith) as well as inventors of new laws.